A cartografia escolar e as práticas docentes nas séries iniciais do ensino fundamental - Oliveira, Adriano Rodrigo (Universidade Federal de São Carlos, 2003)
This work tries to identify the practices that two primary school teachers draw up to promote the specific subject teaching of this series through the usage of municipal maps.We started with a text about the construction of, in Brazil, the research area in the scholar cartography. The formation os a research group originates the production of a Limeira Municipal Atlas at UNESP in Rio Claro. After, we stand out a literature about the construction of the scholar and docent knowledge as well as the discussion about geography and scholar culture. Considering the research goal, we delimit our methodology option to a qualitative approach, using the registers in the diary, and class observation and interviews. The data obtained indicate that the conceptions and the pedagogical models built by the teachers are the generators of the knowledge forms transmitted in the classroom. The usage of maps in education becomes possible two ways of knowledge construction: the first conceives the teaching as the knowledge transmission, and the second as the collective construction. The teacher s knowledge about cartographic language is originated by everyday experiences, this knowledge comes from the learning process with other teacher and usage of pedagogic books. The elements as subtitles and scales are a bit elucidative to the teachers, what makes difficult the teaching of the municipal atlas contents. The atlas creates, in the scholar context, motivating scholar and learning processes because the local problematics are experienced by the teachers and students.
Keywords: Professores - formação; Geografia - ensino; Cartografia; Prática docente; CIENCIAS HUMANAS::EDUCACAO